Characterization of Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Trafficking Reveals a Novel Lysosomal Targeting Mechanism via Amyloid Precursor-like Protein 2 (APLP2) - DeVay, Rachel M.; Shelton, David L.; Liang, Hong (The Journal of biological chemistry, 2013)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates low density lipoprotein receptor protein levels by diverting it to lysosomes. Monoclonal antibody therapeutics aimed to neutralize PCSK9 have been shown to successfully lower serum LDL levels; however, we previously found that such therapeutic antibodies are subject to PCSK9-mediated clearance. In this study, we discovered that PCSK9 interacts via its C-terminal domain directly and in a pH-dependent manner with amyloid precursor protein as well as its closely related family member, amyloid precursor protein-like protein 2. Furthermore, we determined that amyloid precursor protein-like protein-2, but not amyloid precursor protein, is involved in mediating postendocytic delivery of PCSK9 to lysosomes and is therefore important for PCSK9 function. Based on our data, we propose a model for a lysosomal transport complex by which a soluble protein can target another protein for degradation from the luminal side of the membrane by bridging it to a lysosomally targeted transmembrane protein. Background: PCSK9 functions to degrade the LDLR by a previously unknown lysosomal sorting mechanism. Results: Here, we discovered and characterized a novel, pH-dependent interaction between PCSK9 and the amyloid precursor-like protein 2 (APLP2). Conclusion: APLP2 plays an integral role in postendocytic PCSK9 lysosomal sorting. Significance: These findings provide key insights into the mechanism by which PCSK9 degrades LDLR and reveal a novel lysosomal transport complex.